Superconvergence Analysis for Cubic Triangular Element of the Finite Element (Journal of Computational Mathematics, 2000)
In this paper, we construct a projection interpolation for cubic triangular element by using orthogonal expansion triangular method. We show two fundamental formulas of estimation on a special partion and obtain a superconvergence result of 1-ε order higher for the placement function and its tangential derivative on the third order Lobatto points and Gauss points on each edge of triangular element.
Keywords: Finite element; Superconvergence; Projection interpolation.